Positive electrode lithium supplementing material and preparation method thereof, positive electrode plate and lithium ion battery

Through the synergistic cooperation of anion doping and fast ion conductor material coating, the problem of instability and gas production of cathode lithium supplement materials in the air is solved, and the charge and discharge capacity, rate performance and cycle stability of the battery are significantly improved.

CN119361704APending Publication Date: 2025-01-24福建龙净储能电池有限公司 +2
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411511749.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing positive electrode lithium supplement material is unstable in the air, and the gas production process of prelithization affects the lithium supplement effect.

Method used

Through the coordinated coordination of anionic doping and fast ion conductor material, the positive electrode lithium material is formed, the anion is doped in the oxygen position of the lithium iron, and the fast -ion conductor material is covered with air contact to reduce gas production.

Benefits of technology

Significantly improve the charge and discharge capacity, rate performance and cycle stability of the material, enhance the lithium replenishment effect, and extend the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105660910000151
    Figure BDA0005105660910000151
  • Figure BDA0005105660910000161
    Figure BDA0005105660910000161
Patent Text Reader

Abstract

The invention provides a positive electrode lithium supplementing material and a preparation method thereof, a positive electrode plate and a lithium ion battery. The positive electrode lithium supplementing material comprises a lithium supplementing base material and a coating layer coating the surface of the lithium supplementing base material, the lithium supplementing matrix material comprises an anion-doped lithium ferrite material, and the coating layer comprises a fast ion conductor material. According to the positive electrode lithium supplementing material provided by the invention, through the synergistic cooperation of anion doping and fast ion conductor coating, the lithium supplementing effect is good, the influence caused by gas production of the lithium supplementing material can be reduced, and meanwhile, the charge-discharge capacity, the rate capability and the cycle stability of a battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a positive electrode lithium supplement material and a preparation method thereof, a positive electrode plate and a lithium ion battery. Background Art

[0002] During the first charge of a lithium-ion battery, a portion of the active lithium ions will be consumed on the negative electrode surface to form a layer of solid electrolyte interface (SEI), and this part of the lost lithium ions is called irreversible capacity loss, which affects the battery's first charge and discharge efficiency. Lithium replenishment technology increases the content of active lithium sources to pre-compensate for the loss of active lithium during the first week of charge and discharge, improve the first week coulomb efficiency, and thus improve the capacity, cycle life and energy density of lithium batteries.

[0003] Lithium replenishment technology is generally divided into negative electrode lithium replenishment technology and positive electrode lithium replenishment technology. Negative electrode lithium replenishment is to use lithium powder and lithium foil and other processes to replenish lithium, facing the use of lithium metal and the production environment, conventional solvents, binders, air and heat treatment process and other problems. Positive electrode lithium replenishment is generally to add a small amount of positive electrode replenishment material during the positive electrode slurry preparation process for lithium replenishment. In contrast, positive electrode lithium replenishment materials have the advantages of easy synthesis, low price and high lithium replenishment capacity. At the same time, the positive electrode lithium replenishment process can be better compatible with the existing lithium-ion battery manufacturing process. However, positive electrode lithium replenishment faces problems such as poor stability of the lattice oxygen framework, side reactions at the contact interface between the lithium replenishment material and the electrolyte, poor stability of the material in the air, and decomposition and gas production of the lithium replenishment material. Therefore, it has been widely studied.

[0004] The existing positive electrode lithium replenishment is generally done by adding a small amount of positive electrode replenishment materials during the positive electrode slurry preparation process. Lithium ferrite (Li5FeO4) is a lithium metal oxide with an inverse fluorite structure. Its theoretical specific capacity can reach 867mAh / g. It is an ideal positive electrode lithium replenishment material and has been widely studied. However, it faces problems such as instability in the air and gas generation during the pre-lithiation process.

[0005] Therefore, it is necessary to improve the chemical stability and conductivity of Li5FeO4 materials in the air environment and reduce the gas production of Li5FeO4 to enhance the lithium replenishment effect. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a positive electrode lithium supplement material and a preparation method thereof, a positive electrode plate and a lithium ion battery. The positive electrode lithium supplement material provided by the present invention has a good lithium supplement effect through the coordinated cooperation of anion doping and fast ion conductor coating, can reduce the impact of gas production of the lithium supplement material, and can improve the charge and discharge capacity, rate performance and cycle stability of the battery.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a positive electrode lithium supplement material, which includes a lithium supplement matrix material and a coating layer coated on the surface of the lithium supplement matrix material; the lithium supplement matrix material includes anion-doped lithium ferrite material, and the coating layer includes a fast ion conductor material.

[0009] The positive electrode lithium supplement material provided by the present invention cooperates with anion doping and fast ion conductor material coating. Anions are doped in the oxygen position of the lithium ferrite material, which can significantly inhibit the lattice oxygen in the material from participating in redox and reduce oxygen release. At the same time, the reducing anions can enhance the stability of the lattice oxygen framework, thereby stabilizing the material structure. In addition, the reducing anions can also improve the ionic conductivity of the material, improve the electrical conductivity and lithium capacity of the lithium ferrite material, and significantly improve the charge and discharge capacity, rate performance and cycle stability of the material. The fast ion conductor material can promote Li + In the transfer process at the interface between the positive electrode material and the electrolyte, the rate capability of the material is improved; at the same time, the fast ion conductor material can also block the direct contact between the surface of the lithium-supplementing matrix material and water and carbon dioxide in the air, thereby improving the stability of the material in the air. It can also isolate the lithium-supplementing matrix material from the electrolyte, avoiding the occurrence of side reactions at the contact interface and the dissolution of transition metal ions into the electrolyte. The cycle stability is also improved, thereby improving the lithium replenishment effect and achieving an increase in battery capacity, rate and cycle performance.

[0010] In the present invention, anion doping and fast ion conductor material coating cooperate with each other and are indispensable. Without any one of the conditions, the impact of material gas production and environmental reaction cannot be effectively reduced, and the charge and discharge capacity, rate performance and cycle stability of the material cannot be better improved.

[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0012] Preferably, the anions include sulfide ions and / or halogen ions.

[0013] In the present invention, the halogen ion includes but is not limited to at least one of fluoride ion, chloride ion or bromide ion.

[0014] In the present invention, the sulfur ions and / or halogen ions are reducing and can significantly inhibit the lattice oxygen in the material from participating in redox, reduce oxygen release, and at the same time enhance the stability of the lattice oxygen framework, thereby playing a role in stabilizing the material structure; in addition, the sulfur ions and / or halogen ions can also improve the ionic conductivity of the material, improve the electrical conductivity and lithium capacity of the lithium ferrite material, and significantly improve the charge and discharge capacity, rate performance and cycle stability of the material.

[0015] Preferably, the fast ion conductor material comprises a perovskite-type fast ion conductor material, and the perovskite-type fast ion conductor material comprises lithium lanthanum titanium oxide.

[0016] In the present invention, the perovskite fast ion conductor material is selected to promote Li + In the transfer process at the interface between the positive electrode material and the electrolyte, the rate capability of the material is improved; it can also block the direct contact between the surface of the lithium-supplemented matrix material and the water and carbon dioxide in the air, improve the stability of the material in the air, and can also isolate the lithium-supplemented matrix material from the electrolyte to avoid the occurrence of side reactions at the contact interface and the dissolution of transition metal ions into the electrolyte. The use of perovskite-type fast ion conductor materials further achieves the improvement of battery capacity, rate and cycle performance, and in the perovskite-type fast ion conductor materials, in addition to lithium lanthanum titanium oxide (LLTO), other types of substances that can be known to those skilled in the art within a reasonable range are also applicable to the present invention. Further, LLTO is selected, which has high ionic conductivity, chemical stability and thermal stability, is more conducive to improving the conductivity of the positive electrode material, and can also provide a fast channel for lithium ion transfer, improve kinetic performance, and promote the transmission of lithium ions between the positive electrode material and the electrolyte.

[0017] In the present invention, the perovskite fast ion conductor material is specifically Li 0.5 La 0.5 TiO3、Li 0.33 La 0.57 TiO3、Li 0.29 La 0.57 TiO3、Li 0.33 Ba 0.25 La 0.39 TiO3, (Li 0.33 La 0.56 ) 1.005 Ti 0.99 Al 0.01 O3 or Li 0.5 La 0.5 Ti 0.95 Zr 0.05 At least one of O3, etc.

[0018] In a second aspect, the present invention provides a method for preparing the positive electrode lithium supplement material as described in the first aspect, the preparation method comprising the following steps:

[0019] A lithium source, an iron source and an anion doping source are mixed once, and a first sintering is performed to obtain a lithium-supplemented matrix material of anion-doped lithium ferrite material;

[0020] Secondary mixing of the lithium-supplementing matrix material and the coating layer material, and second sintering to obtain the positive electrode lithium-supplementing material;

[0021] Wherein, the coating layer material includes a fast ion conductor material.

[0022] The preparation method provided by the present invention realizes in-situ doping of anions in the lithium ferrite material, and simultaneously realizes tight coating of the fast ion conductor material through the second sintering. The preparation method is simple to operate and is suitable for large-scale production.

[0023] Preferably, the molar ratio of lithium in the lithium source, iron in the iron source and anions in the anion doping source is (5-6):1:(0.05-0.2), for example, 5:1:0.05, 5:1:0.08, 5:1:0.1, 5:1:0.13, 5:1:0.15, 5:1:0.18, 5:1:2, 5.5:1:0.05, 5.5:1:0.08 , 5.5:1:0.1, 5.5:1:0.13, 5.5:1:0.15, 5.5:1:0.18, 5.5:1:2, 6:1:0.05, 6:1:0.08, 6:1:0.1, 6:1:0.13, 6:1:0.15, 6:1:0.18 or 6:1:2, etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In the present invention, by regulating the molar ratio of lithium in the lithium source, iron in the iron source and anions in the anion doping source to be (5-6):1:(0.05-0.2), the doping amount of anions at the oxygen position is further adjusted, thereby better achieving the doping of anions, facilitating processing and manufacturing, and achieving good lithium supplementation effect.

[0025] Preferably, the anion doping source includes a sulfur source and / or a halogen source.

[0026] The present invention does not impose any special restrictions on the specific types of sulfur sources and halogen sources, and any type of material that can achieve anion doping can be used in the present invention.

[0027] For example, the sulfur source includes, but is not limited to, at least one of sodium sulfide, lithium sulfide, thiourea or sodium dodecylbenzene sulfonate.

[0028] For example, the halogen source includes at least one of a fluorine source, a chlorine source, or a bromine source.

[0029] Furthermore, the fluorine source includes but is not limited to at least one of perfluorododecanoic acid, ammonium fluoride or trifluoromethanesulfonic acid, etc.; the chlorine source includes but is not limited to at least one of sodium chloride, potassium chloride or ammonium chloride, etc.

[0030] Preferably, the rotation speed of the primary mixing is 200-300 r / min, for example 200 r / min, 225 r / min, 250 r / min, 275 r / min or 300 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the time for the primary mixing is 5 to 7 hours, such as 5 hours, 6 hours or 7 hours, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] Preferably, the first sintering includes sequentially performing a first stage sintering and a second stage sintering.

[0033] Preferably, the sintering temperature of the first stage sintering is 500-600°C, for example, 500°C, 550°C, 600°C, 650°C or 700°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, the sintering time of the first stage sintering is 4 to 5 hours, such as 4 hours or 5 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] Preferably, the sintering temperature of the second stage sintering is 700-900°C, for example 700°C, 750°C, 800°C, 850°C or 900°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, the sintering time of the second stage sintering is 15 to 20 hours, for example, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours or 20 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the mass ratio of the lithium-supplementing matrix material to the coating layer material is (30-50):(7-12), for example, 30:7, 30:8, 30:9, 30:10, 30:11, 30:12, 35:7, 35:8, 35:9, 35:10, 35:11, 35:12, 40:7, 40:8, 40:9, 40:10, 40:11, 40:12, 45:7, 45:8, 45:9, 45:10, 45:11, 45:12, 50:7, 50:8, 50:9, 50:10, 50:11 or 50:12, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] In the present invention, by adjusting the mass ratio of the lithium-replenishing matrix material to the coating layer material to (30-50):(7-12), it is possible to ensure uniform and complete coating of the coating layer, while avoiding excessive thickness of the coating layer, which affects the amount of lithium-replenishing active substances and thus affects the lithium-replenishing effect; further improving the battery capacity, rate and cycle performance.

[0039] Preferably, the secondary mixing includes liquid phase mixing, and the liquid phase mixing includes: liquid phase mixing of the coating layer material solution and the lithium supplement matrix material solution, and drying the mixed slurry to obtain a secondary mixing product.

[0040] In the present invention, a liquid phase mixing method is used to mix the coating layer material and the lithium supplement matrix material, which is more conducive to the uniformity of coating.

[0041] The present invention does not impose any special limitation on the solvent in the liquid phase mixing process, and is applicable to any type of solvent that can achieve uniform mixing of the two materials. For example, the solvent in the solution includes but is not limited to water and / or ethanol (such as anhydrous ethanol).

[0042] Preferably, the temperature of the liquid phase mixing is 60-70°C, for example 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] Preferably, the sintering temperature of the second sintering is 400-460°C, for example 400°C, 410°C, 420°C, 430°C, 440°C, 450°C or 460°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] Preferably, the sintering time of the second sintering is 5 to 6 hours, such as 5 hours or 6 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0045] In the present invention, after liquid phase mixing, the second sintering is performed, so that the coating stability is better.

[0046] It should also be noted that the lithium source and iron source in the present invention are both conventional technical solutions, and those skilled in the art can make adaptive selections and adjustments based on actual needs.

[0047] The lithium source includes but is not limited to at least one of lithium carbonate, lithium hydroxide monohydrate, lithium bicarbonate or lithium nitrate; the iron source includes but is not limited to at least one of Fe2O3 or Fe2(SO4)3, Fe(NO3)3 or FeCl3.

[0048] The fast ion conductor material in the present invention can be prepared by conventional preparation methods, or can be purchased directly according to demand, and can be adaptively selected and adjusted by those skilled in the art.

[0049] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the positive electrode lithium replenishing material as described in the first aspect or the positive electrode lithium replenishing material prepared by the preparation method as described in the second aspect.

[0050] In a fourth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the third aspect.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] The positive electrode lithium supplement material provided by the present invention cooperates with anion doping and fast ion conductor material coating. Anions are doped in the oxygen position of the lithium ferrite material, which can significantly inhibit the lattice oxygen in the material from participating in redox and reduce oxygen release. At the same time, the reducing anions can enhance the stability of the lattice oxygen framework, thereby stabilizing the material structure. In addition, the reducing anions can also improve the ionic conductivity of the material, improve the electrical conductivity and lithium capacity of the lithium ferrite material, and significantly improve the charge and discharge capacity, rate performance and cycle stability of the material. The fast ion conductor material can promote Li + In the transfer process at the interface between the positive electrode material and the electrolyte, the rate capability of the material is improved; at the same time, the fast ion conductor material can also block the direct contact between the surface of the lithium-supplementing matrix material and water and carbon dioxide in the air, thereby improving the stability of the material in the air. It can also isolate the lithium-supplementing matrix material from the electrolyte, avoiding the occurrence of side reactions at the contact interface and the dissolution of transition metal ions into the electrolyte. The cycle stability is also improved, thereby improving the lithium-supplementing effect and achieving a significant increase in battery capacity, rate and cycle performance. DETAILED DESCRIPTION

[0053] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.

[0055] In the description of this application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary and secondary relationship of the indicated technical features.

[0056] Example 1

[0057] This embodiment provides a positive electrode lithium supplement material, which includes a lithium supplement matrix material and a coating layer coated on the surface of the lithium supplement matrix material; the lithium supplement matrix material includes a lithium ferrite material doped with anionic sulfur ions, and the coating layer includes a fast ion conductor material lithium lanthanum titanium oxide LLTO.

[0058] The preparation method of the positive electrode lithium supplement material is as follows: (1)

[0060] Preparation of lithium-supplementing matrix material: lithium source lithium hydroxide monohydrate, iron source Fe2(SO4)3 and doping source sodium sulfide are mixed evenly in a ball mill according to the atomic ratio (molar ratio) of Li:Fe:S of 5:1:0.08, the ball milling speed is 220r / min, and the ball milling time is 5.5h to obtain a mixture; the mixture is placed in a muffle furnace, and in a protective atmosphere, firstly roasted at a low temperature of 500°C for 5h, and then roasted at 750°C for 18h, and after cooling, crushed, pulverized and sieved to obtain the lithium-supplementing matrix material;

[0061] Preparation of LLTO powder: La(NO3)3, LiNO3 and tetrabutyl titanate were weighed in a mass ratio of 3:11:6, and the weighed La(NO3)3 and LiNO3 were dissolved in anhydrous ethanol and stirred for 30 minutes to obtain an ethanol solution of nitrate, tetrabutyl titanate and acetylacetone were mixed in a mass ratio of 4:2 and stirred for 40 minutes to obtain a tetrabutyl titanate solution, and the ethanol solution of nitrate was added dropwise to the tetrabutyl titanate solution, mixed, and stirred for 1 hour, and the obtained sol was placed in a drying oven for drying at a drying temperature of 65°C and a drying time of 35 hours; after drying, it was allowed to stand at room temperature for 6 days to obtain an LLTO precursor, and the LLTO precursor was fully ground with a mortar, and then placed in a tubular furnace, and calcined at a temperature of 880°C for 7 hours to finally obtain LLTO. (2)

[0063] The lithium-supplementing matrix material and LLTO in a mass ratio of 35:8 were dissolved in anhydrous ethanol respectively, stirred for 7.5 hours, and then both suspensions were heated to 68° C. to obtain LLTO ethanol solution and lithium-supplementing matrix material suspension;

[0064] The LLTO ethanol solution was added dropwise into the lithium-replenishing matrix material suspension using a dropper, and the suspension was stirred at a constant temperature of 62° C. until the suspension became a paste, and then dried in an oven at 70° C. for 15 h. The dried powder was fully ground, and heat treated at 420° C. for 6 h in a tubular atmosphere furnace under a protective atmosphere, and then ground to obtain the positive electrode lithium-replenishing material.

[0065] Example 2

[0066] This embodiment provides a positive electrode lithium supplement material, which includes a lithium supplement matrix material and a coating layer coated on the surface of the lithium supplement matrix material; the lithium supplement matrix material includes a lithium ferrite material doped with anions and fluorine ions, and the coating layer includes a fast ion conductor material lithium lanthanum titanium oxide LLTO.

[0067] The preparation method of the positive electrode lithium supplement material is as follows: (1)

[0069] Preparation of lithium-supplementing matrix material: lithium source lithium hydroxide monohydrate, iron source Fe2(SO4)3 and doping source perfluorododecanoic acid are mixed uniformly in a ball mill according to the atomic ratio of Li:Fe:F of 5.5:1:0.1, the ball milling speed is 250r / min, and the ball milling time is 6h to obtain a mixture; the mixture is placed in a muffle furnace, and in a protective atmosphere, firstly roasted at a low temperature of 550°C for 4.5h, and then roasted at 800°C for 17h, and after cooling, crushed, pulverized and sieved to obtain the lithium-supplementing matrix material;

[0070] Preparation of LLTO powder: La(NO3)3, LiNO3 and tetrabutyl titanate were weighed in a mass ratio of 4:12:7, and the weighed La(NO3)3 and LiNO3 were dissolved in anhydrous ethanol and stirred for 40 minutes to obtain an ethanol solution of nitrate, tetrabutyl titanate and acetylacetone were mixed in a mass ratio of 3:2 and stirred for 35 minutes to obtain a tetrabutyl titanate solution, and the ethanol solution of nitrate was added dropwise to the tetrabutyl titanate solution, mixed, and stirred for 1.5 hours, and the obtained sol was placed in a drying oven for drying at a drying temperature of 70°C and a drying time of 30 hours; after drying, it was allowed to stand at room temperature for 5 days to obtain an LLTO precursor, and the LLTO precursor was fully ground with a mortar, and then placed in a tubular furnace, and calcined at a temperature of 890°C for 6 hours to finally obtain LLTO. (2)

[0072] The lithium-supplementing matrix material and LLTO in a mass ratio of 40:9 were dissolved in anhydrous ethanol respectively, stirred for 6 hours, and then both suspensions were heated to 65° C. to obtain LLTO ethanol solution and lithium-supplementing matrix material suspension;

[0073] The LLTO ethanol solution was added dropwise into the lithium-replenishing matrix material suspension using a dropper, and the suspension was stirred at a constant temperature of 68°C until the suspension became a paste. The suspension was dried in an oven at 73°C for 13 hours, and the dried powder was fully ground. The powder was heat treated at 430°C for 5.5 hours in a tubular atmosphere furnace under a protective atmosphere, and then ground to obtain the positive electrode lithium-replenishing material.

[0074] Example 3

[0075] This embodiment provides a positive electrode lithium supplement material, which includes a lithium supplement matrix material and a coating layer coated on the surface of the lithium supplement matrix material; the lithium supplement matrix material includes a lithium ferrite material doped with anionic sulfur ions, and the coating layer includes a fast ion conductor material lithium lanthanum titanium oxide LLTO.

[0076] The preparation method of the positive electrode lithium supplement material is as follows: (1)

[0078] Preparation of lithium-supplementing matrix material: lithium source lithium hydroxide monohydrate, iron source Fe2(SO4)3 and doping source sodium sulfide are mixed evenly in a ball mill according to the atomic ratio of Li:Fe:S of 5.8:1:0.15, the ball milling speed is 280r / min, and the ball milling time is 5h to obtain a mixture; the mixture is placed in a muffle furnace, and in a protective atmosphere, firstly roasted at a low temperature of 580°C for 4.2h, and then roasted at 880°C for 15h, and after cooling, crushed, pulverized and sieved to obtain the lithium-supplementing matrix material;

[0079] Preparation of LLTO powder: La(NO3)3, LiNO3 and tetrabutyl titanate were weighed in a mass ratio of 5:14:9, and the weighed La(NO3)3 and LiNO3 were dissolved in anhydrous ethanol and stirred for 45 minutes to obtain an ethanol solution of nitrate, tetrabutyl titanate and acetylacetone were mixed in a mass ratio of 4.5:2 and stirred for 40 minutes to obtain a tetrabutyl titanate solution, and the ethanol solution of nitrate was added dropwise to the tetrabutyl titanate solution, mixed, and stirred for 1.7 hours, and the obtained sol was placed in a drying oven for drying at a drying temperature of 75°C and a drying time of 25 hours; after drying, it was allowed to stand at room temperature for 7 days to obtain an LLTO precursor, and the LLTO precursor was fully ground with a mortar, and then placed in a tubular furnace, and calcined at a temperature of 900°C for 5 hours to finally obtain LLTO. (2)

[0081] The lithium-replenishing matrix material and LLTO in a mass ratio of 45:11 were dissolved in anhydrous ethanol respectively, stirred for 7.5 hours, and then both suspensions were heated to 68° C. to obtain LLTO ethanol solution and lithium-replenishing matrix material suspension;

[0082] The LLTO ethanol solution was added dropwise into the lithium-replenishing matrix material suspension using a dropper, and the suspension was stirred at a constant temperature of 68°C until the suspension became a paste. The suspension was dried in an oven at 78°C for 12 hours, and the dried powder was fully ground. The powder was heat treated at 450°C for 5.8 hours in a tubular atmosphere furnace under a protective atmosphere, and then ground to obtain the positive electrode lithium-replenishing material.

[0083] Example 4

[0084] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the atomic ratio of Li:Fe:S is 5:1:0.2.

[0085] The rest of the preparation methods and parameters were the same as those in Example 1.

[0086] Example 5

[0087] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the atomic ratio of Li:Fe:S is 5:1:0.05.

[0088] The rest of the preparation methods and parameters were the same as those in Example 1.

[0089] Example 6

[0090] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the atomic ratio of Li:Fe:S is 5:1:0.3.

[0091] The rest of the preparation methods and parameters were the same as those in Example 1.

[0092] Example 7

[0093] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the atomic ratio of Li:Fe:S is 5:1:0.03.

[0094] The rest of the preparation methods and parameters were the same as those in Example 1.

[0095] Example 8

[0096] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the mass ratio of the lithium-supplemented matrix material to LLTO is 35:5.

[0097] The rest of the preparation methods and parameters were the same as those in Example 1.

[0098] Example 9

[0099] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the mass ratio of the lithium-supplemented matrix material to LLTO is 35:15.

[0100] The rest of the preparation methods and parameters were the same as those in Example 1.

[0101] Example 10

[0102] The difference between this embodiment and embodiment 1 is that the fast ion conductor material in this embodiment is garnet-type LLZO (Li7La3Zr2O 12 ), commercially available).

[0103] The rest of the preparation methods and parameters were the same as those in Example 1.

[0104] Comparative Example 1

[0105] The difference between this comparative example and Example 1 is that in the positive electrode lithium supplement material provided in this comparative example, the lithium supplement matrix material is undoped lithium ferrite;

[0106] In the preparation method, the doping source sodium sulfide is not added in step (1).

[0107] The rest of the preparation methods and parameters were the same as those in Example 1.

[0108] Comparative Example 2

[0109] The difference between this comparative example and Example 1 is that the positive electrode lithium supplement material provided in this comparative example does not contain a coating layer.

[0110] In the preparation method, the preparation process of LLTO in step (1) is not carried out, and step (2) is not carried out.

[0111] The rest of the preparation methods and parameters were the same as those in Example 1.

[0112] The positive electrode lithium replenishing materials provided in Examples 1-10 and Comparative Examples 1-2 are used in positive electrode lithium replenishing, and the specific applications are as follows:

[0113] Application Example 1

[0114] This application example provides a battery, and the preparation method of the battery includes:

[0115] Positive electrode preparation: lithium iron phosphate, the positive electrode lithium supplement material provided in Example 1, CNT, conductive carbon black and polyvinylidene fluoride binder were mixed in a mass ratio of 94.8:2:0.5:0.7:2, NMP solvent was added, and the mixture was stirred under the action of a vacuum stirrer until the system was uniform to obtain a positive electrode slurry, and the positive electrode slurry was evenly coated on one side of the positive electrode current collector aluminum foil, and dried, and then rolled to obtain a positive electrode sheet;

[0116] Preparation of negative electrode sheet: lithium sheet is selected as negative electrode sheet;

[0117] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0118] Preparation of diaphragm: Polypropylene film is selected as the diaphragm.

[0119] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell;

[0120] The bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a CR2032 button battery is obtained.

[0121] Application Example 2-10 and Comparative Application Example 1-2

[0122] The difference between Application Example 2-10 and Comparative Example 1-2 and Application Example 1 is that the positive electrode lithium supplement materials provided by Example 2-10 and Comparative Example 1-2 are added respectively in the positive electrode sheet preparation stage.

[0123] The rest of the preparation methods and parameters are consistent with those in Application Example 1.

[0124] Control group

[0125] The difference between this control group and Application Example 1 is that no positive electrode lithium supplement material is added to this control group, and the mass ratio of lithium iron phosphate, CNT, conductive carbon black and polyvinylidene fluoride binder is adjusted to 96.8:0.5:0.7:2.

[0126] The rest of the preparation methods and parameters are consistent with those in Application Example 1.

[0127] The batteries of application examples 1-10, comparative application examples 1-2 and the control group were subjected to performance tests under the following test conditions:

[0128] a) First round capacity test:

[0129] At 25℃, charge to 4.1V at 0.1C constant current and constant voltage, cut off current to 0.05C, leave for 30min, and discharge to 2.5V at 0.1C constant current.

[0130] b) 500-week cycle test:

[0131] Cycle test: 25℃, charge to 3.65V at 1C constant current and constant voltage, cut off current 0.05C, stand for 30min, discharge to 2.5V at 1C constant current, repeat 200 times.

[0132] c) Rate performance:

[0133] At 25℃, charge to 3.65V at 0.5C constant current and constant voltage, cut off current 0.05C, leave for 10min, discharge to 2.5V at 0.5C constant current, leave for 10min.

[0134] Charge to 3.65V at 0.5C constant current and constant voltage, cut off current at 0.05C, leave for 10 minutes, discharge to 2.5V at 1C constant current, leave for 10 minutes.

[0135] Charge to 3.65V at 0.5C constant current and constant voltage, cut off current at 0.05C, leave for 10min, discharge to 2.5V at 2C constant current, leave for 10min.

[0136] Charge to 3.65V at 0.5C constant current and constant voltage, cut off current at 0.05C, leave for 10 minutes, discharge to 2.5V at 3C constant current, leave for 10 minutes.

[0137] The test results of the above tests are shown in Table 1.

[0138] Table 1

[0139]

[0140]

[0141] In summary, the positive electrode lithium replenishing material provided by the present invention cooperates with anion doping and fast ion conductor material coating to enhance the lithium replenishing effect and achieve a substantial improvement in battery capacity, rate and cycle performance.

[0142] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A positive electrode lithium supplement material, characterized in that: The positive electrode lithium supplement material comprises a lithium supplement matrix material and a coating layer coated on the surface of the lithium supplement matrix material; the lithium supplement matrix material comprises anion-doped lithium ferrite material, and the coating layer comprises a fast ion conductor material.

2. The positive electrode lithium supplement material according to claim 1, characterized in that: The anions include sulfide ions and / or halogen ions.

3. The positive electrode lithium supplement material according to claim 1 or 2, characterized in that: The fast ion conductor material includes a perovskite-type fast ion conductor material, and the perovskite-type fast ion conductor material includes lithium lanthanum titanium oxide.

4. A method for preparing a positive electrode lithium supplement material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: A lithium source, an iron source and an anion doping source are mixed once, and a first sintering is performed to obtain a lithium-supplemented matrix material of anion-doped lithium ferrite material; Secondary mixing of the lithium-supplementing matrix material and the coating layer material, and second sintering to obtain the positive electrode lithium-supplementing material; Wherein, the coating layer material includes a fast ion conductor material.

5. The preparation method according to claim 4, characterized in that: The molar ratio of lithium in the lithium source, iron in the iron source, and anions in the anion doping source is (5-6):1:(0.05-0.2); Preferably, the anion doping source includes a sulfur source and / or a halogen source; Preferably, the rotation speed of the primary mixing is 200-300 r / min, and the time of the primary mixing is 5-7 h.

6. The preparation method according to claim 4 or 5, characterized in that: The first sintering includes sequentially performing a first stage sintering and a second stage sintering; Preferably, the sintering temperature of the first stage sintering is 500-600°C, and the sintering time of the first stage sintering is 4-5h; Preferably, the sintering temperature of the second stage sintering is 700-900° C., and the sintering time of the second stage sintering is 15-20 hours.

7. The preparation method according to claim 4, characterized in that: The mass ratio of the lithium-supplementing matrix material to the coating layer material is (30-50):(7-12); Preferably, the secondary mixing includes liquid phase mixing, and the liquid phase mixing includes: liquid phase mixing of the coating layer material solution and the lithium supplement matrix material solution, and drying the mixed slurry to obtain a secondary mixing product; Preferably, the temperature of the liquid phase mixing is 60-70°C.

8. The preparation method according to claim 4 or 7, characterized in that: The sintering temperature of the second sintering is 400-460° C., and the sintering time of the second sintering is 5-6 hours.

9. A positive electrode sheet, characterized in that: The positive electrode plate includes the positive electrode lithium replenishing material according to any one of claims 1 to 3 or the positive electrode lithium replenishing material prepared by the preparation method according to any one of claims 4 to 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 9.

Citation Information

Cited By

  • Lithium-rich lithium ferrite lithium supplement agent as well as synthesis method and application thereof

    CN119905695A

  • A lithium-rich lithium ferrite lithium supplement and its synthesis method and use

    CN119905695B

  • Composite coated high-performance lithium-rich lithium ferrite material as well as preparation method and application thereof

    CN120749155A